CO2-responsive polyacrylamide copolymer vesicles with acid-sensitive morpholine moieties and large hydrophobic RAFT end-group. (December 2017) - Chalmers, Benjamin A.; Magee, Christopher; Cheung, David L.; Zetterlund, Per B.; Aldabbagh, Fawaz
Graphical abstract: Highlights: Morpholine is used as the CO2 -responsive part of amphiphilic copolymers. The order of RAFT polymerization greatly effects polyacrylamide self-assembly. Cleavage of the RAFT-end group revert ABA′ morphologies to simpler spherical vesicles. CO2 -irreversibly shifts self-assembly to lower order morphologies. Abstract: Sequential Reversible Addition Fragmentation Chain Transfer (RAFT) polymerizations using 2, 2′-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride (VA-044) and 2-(dodecylthiocarbonothioylthio)-2-methylpropionic acid (DDMAT) were used to give amphiphilic polyacrylamide block copolymers containing N -(2-morpholin-4-ylethyl)acrylamide (MEA), where the morpholine moieties are CO2 -responsive. The order in which monomers were polymerized determined the placement of the large hydrophobic RAFT end group with more complex ABA′ type self-assembly (e.g. patterned and large worm-like vesicles, large compound micelles) obtained when the dodecyl trithiocarbonate end-group was attached to the hydrophilic poly(MEA) block. Cleaving the hydrophobic end group reverts self-assembly to simpler spherical vesicles observed in the triblock of the same chemical composition, but with the RAFT end group attached to the hydrophobic poly( tert -butyl acrylamide) block. Ionization of the hydrophilic poly(MEA) block through flushing with CO2 irreversibly shifts self-assembly towards lower order morphologies with spherical micelles being more favoured than vesicles.